Iguratimod as an alternative induction therapy for refractory lupus nephritis: a preliminary investigational study - Yuening Kang; Qingran Yan; Qiong Fu; Ran Wang; Min Dai; Fang Du; Qing Dai; Ping Ye; Chunmei Wu; Liangjing Lu; Chunde Bao (Arthritis Research & Therapy, 2020)
Abstract Objectives Iguratimod, a novel immunomodulatory agent for rheumatoid arthritis, has been shown to be effective against murine lupus. The aim of this study was to make a preliminary evaluation of the efficacy and safety of iguratimod as salvage therapy in patients with refractory lupus nephritis (LN). Methods We enrolled eligible patients with refractory LN, which we defined as having failed or relapsed on at least two immunosuppressant agents. After enrollment, we substituted iguratimod (25 mg twice daily) for their previous immunosuppressant agents without increasing the dose of steroids. The primary outcome was complete/partial remission (PR/CR) at week 24. Patients who achieved remission continued iguratimod as maintenance therapy over an extended follow-up. Results The study cohort comprised 14 patients with refractory LN, 10 of whom had recent treatment failure and 4 repeated relapses with inadequate initial responses. At enrollment, none of the patients had detectable evidence of extra-renal involvement. The median prednisone dosage was 10 mg/d (IQR 0–10 mg/day). Thirteen patients were eligible for response evaluation, with one patient missed. The renal response rate was 92.3% (12/13) at week 24, with 38.5% (5/13) achieving CR and 53.8% (7/13) achieving PR. We then continued to follow up the responding patients for up to 144 weeks. Twenty-five percent of the patients (3/12) had renal relapse after initial PR. The estimated glomerular filtration rate of all patients maintained stable during follow-up. One patient had a severe adverse reaction (anemia) but recovered fully after stopping iguratimod. Conclusions Our study supports the potential of iguratimod for treatment of refractory LN. Iguratimod could be a promising candidate drug for this condition.